Implementasi Education For Sustainable Development (ESD) pada universitas lintas negara terhadap tingkat pengetahuan dan perilaku kesadaran lingkungan mahasiswa - Nur Hamidah; Hertien Koosbandiah Surtikanti; Riandi (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Environmental awareness is fundamental considering its impact on the survival of all creatures on Earth. This scoping review article aims to construct an effective and comprehensive approach to increase student environmental awareness. The writing of this article refers to the systematic review scoping method with five stages, those are topic selection, literature search, literature selection, literature assessment, and the last is analysis and synthesis of literature. The synthesis of this article focuses on research results from all aspects related to the environment as the dependent variable. Sixteen research articles published by international journals with a focus on environmental themes are the main data sources in this article. The synthesis of the 16 data sources resulted a summary of the implementation, evaluation, influencing factors as well as strategies in increasing environmental awareness from various articles and construct more effective environmental awareness approach.